Intruder alarms - Honey, G. (Newnes, 2003)
Intruder Alarms provides a definitive and fully up-to-date guide to the specification, systems design, integration, installation and maintenance of intruder alarm systems. It has been written to be the essential handbook for installation engineers and security professionals working in this rapidly expanding and developing area. The second edition includes new material on the use of remote signalling and networking and an expanded section on the integration of security systems, including real-world case studies. Information on police response policy, and the use of confirmed alarm technology has been updated, along with coverage of accreditation systems, NSI and ICON. This book has been endorsed by SITO (the UK's Security Industry Training Organisation) as a suitable text for students following the relevant SITO courses including the SITO / City & Guilds scheme 1851: Knowledge of Security and Emergency Alarm Systems. * The practical guide for installation engineers and security professionals * Essential reading for anyone responsible for the commissioning and maintenance of security alarm systems * New edition covers networking and integration issues.